Redefining of concepts of nursing's meta-paradigm from the perspective of Islam - Zahra Rooddehghan; Nahid Dehghan Nayeri; Ahmad Reza Okhovat (Tehran University of Medical Sciences, 2016)
Background & Aim: The four elements of the nursing meta-paradigm, namely, human, health, environment, and nursing have attracted much attention in the West for years. This study redefined the meta-paradigm or core concepts of nursing from the perspective of Islam. Methods & Materials: A qualitative content analysis was used to collect and analyze data. Data collection were based on in-depth semi-structured individual interviews and focus groups with religious experts and nursing faculty members with many years of experience in training nurses and providing clinical patient care. The samples were selected purposefully and to the extent that data saturation was reached. The data were analyzed using deductive content analysis. Results: Human in the Islamic model of care, the concept "human being" describes a creature capable of growing unified and holistic; capable of acting, choosing, and willing; and God's successor who was assigned to reach a goal by God, and the human should move on the path to the goal. From the perspective of Islam, "health" encompasses sickness and disease in a holistic view that considers illness as a path to blessings, and purification of the heart (and spirit or mind). The environment includes not only the physical world but also the metaphysical world. Based on the Islamic model, all creatures are interconnected through webs of relationships that connect across space and time. Finally, "nursing" is a reciprocal relationship between the nurse and patient that optimally leads to (mutual) growth. The concept of nursing encompasses caring that includes God, through the establishment of win-win relationships with patients (and their families) through prayer, caregiving, and professional behaviors, and actions associated with faith and Godliness in Islam. Conclusion: In the Islamic worldview, not only the nursing meta-paradigms but also the whole universe has been formed on the basis of the monotheism core concept that is different from the Western philosophy. Thus, redefinition of nursing meta-paradigmatic concepts on a monotheistic basis in Islamic countries is of special importance. Redefining nursing Islamic meta-paradigm is beneficial for both Muslim and non-Muslim countries, because it can promote understanding and exchanging of dialogue between nursing scholars and health care professionals and also it can introduces a new point of view about human, sickness and health, environment, and care for them. Hence, this article can be helpful for cross-cultural nursing because understanding the differences and commonalities between cultures can help us go beyond our differences and share our common values to deliver person-entered care. In fact, as Muslims benefit from Western models, non-Muslims can use this concept to provide care to their patients, too.